2008
DOI: 10.1021/np070377j
|View full text |Cite
|
Sign up to set email alerts
|

Combretastatin Dinitrogen-Substituted Stilbene Analogues as Tubulin-Binding and Vascular-Disrupting Agents

Abstract: Several stilbenoid compounds having structural similarity to the combretastatin group of natural products and characterized by the incorporation of two nitrogen-bearing groups (amine, nitro, serinamide) have been prepared by chemical synthesis and evaluated in terms of biochemical and biological activity. The 2',3'-diamino B-ring analogue 17 demonstrated remarkable cytotoxicity against selected human cancer cell lines in vitro (average GI 50 = 13.9 nM) and also showed good activity in regard to inhibition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…For the synthesis of the dinitro compound 173, 4-methoxy-2-nitro-benzealdehyde (171) was treated with nitric acid in fuming sulphuric acid (Scheme 12). 105 An approximately 1:1 mixture of the 2,3-and 2,5-dinitro benzadehydes, 172 and 173, were isolated. Roughly 10% of the aldehydes were oxidized to the benzoic acid observed by 1 H-and 13 C-NMR analyses.…”
Section: Synthesis and Biological Evaluation Of Combretastatin A-1 Anmentioning
confidence: 99%
“…For the synthesis of the dinitro compound 173, 4-methoxy-2-nitro-benzealdehyde (171) was treated with nitric acid in fuming sulphuric acid (Scheme 12). 105 An approximately 1:1 mixture of the 2,3-and 2,5-dinitro benzadehydes, 172 and 173, were isolated. Roughly 10% of the aldehydes were oxidized to the benzoic acid observed by 1 H-and 13 C-NMR analyses.…”
Section: Synthesis and Biological Evaluation Of Combretastatin A-1 Anmentioning
confidence: 99%
“…Among these, compounds 7-10 , 13 , 15 , 15,16 32 , 42,43 33 , 37 , 39 , 46,47 3' CA4-amine, 3' CA4-L-serinamide and AVE8062 36,53 were re-synthesized for the purpose of further biological evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…34 Subsequently, our studies showed that the di-amino variant of combretastatin A-1 (CA1-diamine, Fig. 1 ) 16 was strongly cytotoxic against human cancer cell lines (average GI 50 = 13.9 nM) and also demonstrated potent activity in regard to inhibition of tubulin assembly (IC 50 = 2.8 μM). 16 It is fairly common for compounds that interact with tubulin in the low μM range (cell free assay) to demonstrate nM cytotoxicity against human cancer cell lines; a variety of factors are postulated to influence this activity differential.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations